докажиите тождествa
a)(x+y)(x-y)+(y+a)(y-a)=(x-a)(x+a)
б) (2x-y)(2x+y)+(y-z)(y+z)+(z-2x)(z+2x)=0

софа07022007 софа07022007    1   04.04.2020 22:20    0

Ответы
BlackVaiNor BlackVaiNor  12.10.2020 14:36
А)(х+у)(х-у)+(у+а)(у-а)=(х-а)(х+а)

((х+у)(х-у)+(у+а)(у-а))-((х-а)(х+а))=(х2-у2+у2-а2)-(х2-а2)=(х2-а2)-(х2-а2)=
=х2-а2-х2+а2=0
ответ:тождество доказано

б)(2х-y)(2х+у)+(у-z)(y+z)+(z-2x)(z+2x)=0

(2х-y)(2х+у)+(у-z)(y+z)+(z-2x)(z+2x)-0=
=4x2-y2+y2-z2+z2-4x2-0=0-0=0
ответ тождество доказано.

(4х2-4х в квадрате)
ПОКАЗАТЬ ОТВЕТЫ
cheburejp00xj4 cheburejp00xj4  12.10.2020 14:36

а)

(x+y)(x-y)+(y+a)(y-a)=(x-a)(x+a);\\x^{2}-y^{2}+y^{2}-a^{2}=x^{2}-a^{2};\\x^{2}-a^{2}=x^{2}-a^{2}\\

Истинно, доказано.

б)

(2x-y)(2x+y)+(y-z)(y+z)+(z-2x)(z+2x)=0;\\4x^{2}-y^{2}+y^{2}-z^{2}+z^{2}-4x^{2}=0;\\4x^{2}-4x^{2}+y^{2}-y^{2}+z^{2}-z^{2}=0;\\0=0

Истинно, доказано.

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра